2002
DOI: 10.1177/002242780203900201
|View full text |Cite
|
Sign up to set email alerts
|

Illegal Acts Committed by Adolescents Under the Influence of Alcohol and Drugs

Abstract: This study examined the proximal effects of alcohol and drug use on adolescent illegal activity. Four years of longitudinal data from the Pittsburgh Youth Study were analyzed for 506 local male adolescents. Participants reported committing offenses against persons more often than general theft under the influence of alcohol or drugs. Aggressive acts were more often related to self-reported acute alcohol use than to marijuana use. Those who reported committing illegal acts under the influence reported committin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Indermaur (1995) found that instrumental violence is more often associated with property crime. Raskin White et al (2002) associated drug and alcohol use with violent offenses rather than with property crime. These findings suggest that the organized pattern of perpetrating crime is more likely to involve offenses that seek to acquire goods or money, whereas the disorganized pattern is more likely to involve violent offenses (see Note 5).…”
Section: Discussionmentioning
confidence: 99%
“…Indermaur (1995) found that instrumental violence is more often associated with property crime. Raskin White et al (2002) associated drug and alcohol use with violent offenses rather than with property crime. These findings suggest that the organized pattern of perpetrating crime is more likely to involve offenses that seek to acquire goods or money, whereas the disorganized pattern is more likely to involve violent offenses (see Note 5).…”
Section: Discussionmentioning
confidence: 99%
“…White et al [89] found that male adolescents with heavy alcohol use who were more impulsive and associated with more deviant peers were more likely to commit illegal acts while under the influence of alcohol. Both male and female adolescents who drink heavily have significantly higher rates of violent and property offenses [90], although the relationship between binge drinking and delinquency seems to be stronger for males [91].…”
Section: Legal Problems Including Underage Drinking and Duimentioning
confidence: 94%
“…Pre-adult Exposure to Marijuana: Relationships with Aggressive Behavior 36 different relationship between marijuana use and violent crime arrest rates or violent crime rates may apply to adolescents (Pacula & Kilmer, 2003); in addition, intoxication during fighting is more frequently associated with alcohol use than with marijuana use in adolescents (White, Tice, Loeber, & Stouthamer-Loeber, 2002).…”
Section: Accepted Manuscriptmentioning
confidence: 99%